The Relationship of Physical Quality of The House with The Comfort Level of Occupants Of The House In Dense Area - Khairiyah, Jumiatul; Imam Santoso; Rahmawati, Rahmawati; Erminawati, Erminawati (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2023)
Socially, housing is a fundamental necessity for every individual. As the population in Keraton Subdistrict, Martapura District, continues to grow, the layout and environmental conditions of settlements, characterized by closely arranged buildings, impact the comfort of residents. Habitable living spaces must fulfill health and comfort criteria, influenced by lighting, temperature, and humidity. This research aims to explore the relationship between these factors and residents' comfort levels in densely populated areas. Conducted as an analytical cross-sectional study, the research involved 96 households selected through purposive sampling. Data collection relied on a questionnaire assessing residents' comfort levels, with statistical analysis employing the Sommers’s correlation test. Findings revealed an average lighting intensity of 58.38 Lux, an average temperature of 28.3 °C, and an average humidity of 72% among respondents. Approximately 48 individuals (50%) reported being comfortable living in dense residential areas. Statistical analysis indicated a significant relationship between lighting and residents' comfort levels, while no significant correlation was found between temperature and comfort. However, humidity showed a notable association with residents' comfort. Recommendations for the public include enhancing indoor lighting, regulating temperature, and optimizing humidity levels through daily ventilation through window openings. This approach facilitates better airflow, thereby improving the overall comfort of household occupants. Further research could delve into additional factors influencing residents' comfort and explore alternative strategies to enhance living conditions in densely populated areas. Ultimately, this study underscores the importance of considering environmental factors in urban planning to ensure residents' well-being and comfort.